Game-Tailored Instruction Run by A Foreign English Teacher: Are the Students Engaged and Motivated? - Damar Isti Pratiwi; Akbar Zulkarnain; Ilham Satrio Utomo (Research And Innovation In Language Learning (RILL), 2021)
Motivating students to speak in the classroom is a daunting task faced by many language teachers worldwide (Ulla, 2020). However, investigation reporting motivation among EFL class taught by foreign teachers are rarely revealed. Thus, this study investigates English speaking class taught by a foreign English teacher and students motivation during the program. The participants were freshmen in the academic year of 2019/2020 (N=48). It was conducted on the bridging time of the 1st and 2nd semester (January March 2020). This study applied observation class and a survey method to collect the data. The observation class revealed the method and strategy used by a foreign English teacher, while the survey utilized a 5-scale Likert questionnaire. The results showed that the teacher implemented several game-based strategies in class combined with topic based on the context. The survey acknowledged that the students had high motivation in speaking English. These results shed light on the speaking class design and material in engaging students learning motivation which has to be fun, interesting and fit with the context